Теоретичні основи сталого розвитку в управлінні підприємством - Сталінська, О. В.; Драчук, Ю. З. (Видавництво Львівської політехніки, 2015)
Розглянуто теоретичні основи сталого розвитку в управлінні підприємством для обґрунтування процесу визначення перспективного напряму розвитку підприємства і прийняття управлінських рішень, підпорядкованих меті сталого розвитку як стратегічному пріоритету, що забезпечує його ринкову вартість і суспільну цінність. The theoretical basis for sustainable development as a new model of economic forms of social equality and environmental sustainability is part of the further global development. Every day more and more are gaining strength factors causing the need for change: production and consumption patterns, lack of resources, changes in the global economy, the environment, the dynamics of political processes, as well as demographic changes. The current situation actualizes the need to change management principles and consumption, but also opens up opportunities for new technologies in the market, new growth, and jobs created with the advent of innovative products and services. Sustainable development is reduced to the question of the ability of people, companies and governments to determine their own future. With regard to business participation in the sustainable development means understanding the long-term problems of the planet and in consideration of their policies and practices. Modern business is the process of creating and sharing your own values for long-term sustainability, in addition to economic benefits, it should also take into account the value of the two components: people for whom it is created, and the environment, bringing thus the triple bottom line activities. The problem concerns the stability of the business environment in all its dimensions: social, economic, cultural and environmental. Sustainable development of a certain level, of course, serves as a basis for the sustainable development of its higher levels. So important is the process of integrating the paradigm of sustainable development in the strategic management of the company and its impact on sustainable development of the region, the state of the planet. Companies have a direct and indirect impact on the various stakeholders in the regions of its presence. This includes the impact of social, environmental and economic aspects. Direct impact - the impact that the company itself has on employees and their families, organizations and local communities, as well as local authorities. Indirect effects - the impact that has on the enterprise local population and local authorities, enterprise vendors. Together, this creates the overall effect is that the company has on the region. The analysis shows that there is not a generalized coherent picture that characterizes the multifaceted strategy for sustainable development of industrial enterprises, nor even a general understanding of how the sustainable development in practice. Sustainable development can improve the efficiency of enterprise management, and preferably not in the present or in the near future and in the long term, reduce risk, stabilize the financial situation, to reduce the negative impact on the environment, increase the flexibility of responding to the disturbance of the environment, increase social stability in the enterprise. The urgency and the need to develop a mechanism for strategic management of the enterprises on the principles of sustainable development allows enterprises to study and planning of environmental and social activities, and to plan a withdrawal owners. The implementation of the mechanism will enhance the sustainability of the company both in the short and long term. Using the mechanism of strategic management of the enterprises on the principles of sustainable development will enable a comprehensive and systematically take into account the relationship of factors external and internal environment of the enterprise to the achievement of sustainable development priorities. Accounting basics of the strategic management of enterprises on the principles of sustainable development on the scale of the national economy and related industries will provide the balance between the interests of business owners, the needs of current and longterm operation, as well as environmental protection and social development with a view to overcoming the economic, environmental and social crisis.
Theoretical basis of sustainable development in enterprise management
Keywords: сталий розвиток; теоретичні основи; підприємство; стратегічний пріоритет; управлінські рішення; науковий напрям; sustainable development; theoretical foundations; enterprise strategic priority; management decisions; scientific derection